Strength Development of High Performance Concrete Utilising Micro Pofa - Wan Nur Firdaus, Wan Hassan; Mohamed A., Ismail; Han, Seung Lee; Mohd Warid, Hussin; Khairunisa, Muthusamy (Penerbit UMP, 2018)
The increasing consumption of non-renewable materials for the production of construction materials to support the growing construction industry and its influence on global warming and climate change is a non-trivial matter. Concern towards preserving natural resources and mitigating the undesirable effect of the production of such materials associated with it to the environment apart from ensuring the well-being of the surrounding community has motivated the authorities to encourage the use environmentally friendly construction materials. Owing to the aforementioned circumstances, there is a renewed interest amongst the research community on the development of sustainable building materials. Therefore, the development of sustainable special concretes is in line with Malaysian government’s policy, particularly in aiding the government in their bid to achieve the UN Sustainable Development Goals. Special concrete offers unique benefits in terms of strength, durability, economical design and cost as compared to conventional concrete which is widely used. Moreover, the addition or replacement of wastes to produce such special concrete provides an avenue for a more constructive or innovative means on the utilisation of locally generated waste materials. This book details on the research and development that has been carried out in the area of special concrete viz. blended cement concrete, lightweight aggregate concrete, polymer concrete, high-performance concrete and geopolymer concrete in Malaysia. It compiles the results of past investigations carried out by researchers from the Faculty of Civil Engineering of both UMP as well as UTM. The desirable characteristics of these concretes are highlighted in six different chapters to encourage the industry to venture into these new technologies which are not uncommon in many developed countries. It was demonstrated through the case studies presented that the incorporation of a suitable proportion of locally generated waste material enhances the performance of the aforesaid special concretes. Chapter 1 introduces the notion of utilising ceramic wastes as partial cement replacement which enhances the strength performance of concrete. The effect of micro palm oil fuel ash (POFA) as a mineral admixture in enhancing the properties of high-performance concrete is highlighted in chapter 2. Accordingly, chapter 3 investigates the contribution of kenaf fibre towards the properties of oil palm shell (OPS) reinforced concrete. Chapter 4 evaluates the durability of OPS lightweight aggregate concrete that utilises POFA as partial cement replacement in aggressive environments. The realisation of the need for discovering alternative material to replace cement as a binding agent in concrete has led to the investigation of the development of epoxy-modified mortar which exhibits superior strength in comparison to normal mortar is extensively deliberated in chapter 5. The final chapter, i.e. chapter 6 also discusses the performance of zero cement geopolymer concrete containing alternative admixtures. It is hoped that the readers of this book would benefit from the variety of themes presented, and perhaps may further explore the effect of waste materials in the development of sustainable special concrete from different domains/aspects.